Pengaruh Gaya Kepemimpinan, Kompensasi, Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan PT Jinheung Electric Indonesia di Era Pandemi Covid-19 - Ai Nurhasanah; Sri Wahyuningsih (Departement of Mathematics Education, 2023)
This research was conducted and carried out to determine the effect of leadership style, competence, motivation and work discipline on the performance of employees of PT Jinheung Electric Indonesia in the era of the co-19 pandemic. The next objective is to find out the company's actions in improving the performance of PT Jinheung Electric Indonesia's employees in the era of the co-19 pandemic, and the final goal is to find out the concepts used to improve the performance of PT Jinheung Electric Indonesia's employees in the era of the co-19 pandemic. This type of research is quantitative, which means the data used for the population and research sample. The population used is all employees who work at PT Jinheung Electric Indonesia, totaling 250 employees as the research population because it is a place where researchers work and there are still many problems related to the work productivity of its employees. The technical data collection applied and carried out in this study was carried out through observation, questionnaires and other methods. The data analysis methods used in data processing in this study include instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing.